2019
DOI: 10.3390/e21040428
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Investigation of an Integrated Solar Combined Cycle with an ORC System

Abstract: An integrated solar combined cycle (ISCC) with a low temperature waste heat recovery system is proposed in this paper. The combined system consists of a conventional natural gas combined cycle, organic Rankine cycle and solar fields. The performance of an organic Rankine cycle subsystem as well as the overall proposed ISCC system are analyzed using organic working fluids. Besides, parameters including the pump discharge pressure, exhaust gas temperature, thermal and exergy efficiencies, unit cost of exergy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Hot wind, an energy source containing both low-gradient thermal energy and disordered wind energy, widely exists in industrial scenarios. 22,23 It has been neglected and emitted directly (or after simple treatment) to the external surroundings due to the lack of appropriate energy harvesting technology, which not only leads to the secondary waste of energy, but also exerts adverse effects on the atmosphere. Aiming at the widespread hot wind energy, this work proposes a feasible solution: integrating a TENG and a ThEG to develop a hybrid self-powered system to simultaneously realize hot wind energy harvesting and hot wind information sensing, promoting the transformation from the industrial era to the IoTs era, as manifested in Fig.…”
Section: Scene Illustration and Overall Structurementioning
confidence: 99%
“…Hot wind, an energy source containing both low-gradient thermal energy and disordered wind energy, widely exists in industrial scenarios. 22,23 It has been neglected and emitted directly (or after simple treatment) to the external surroundings due to the lack of appropriate energy harvesting technology, which not only leads to the secondary waste of energy, but also exerts adverse effects on the atmosphere. Aiming at the widespread hot wind energy, this work proposes a feasible solution: integrating a TENG and a ThEG to develop a hybrid self-powered system to simultaneously realize hot wind energy harvesting and hot wind information sensing, promoting the transformation from the industrial era to the IoTs era, as manifested in Fig.…”
Section: Scene Illustration and Overall Structurementioning
confidence: 99%
“…A number of scholars have already performed a lot of research in this direction. Wang et al [20] derived a novel ISCC system with low temperature waste heat utilization by superimposing the ORC on the bottom cycle, and the results showed that under the condition that the DNI was 800 W/m 2 , the minimum exhaust gas temperature of this system was 65.89 • C, the maximum thermal efficiency was 58.33%, the exergy efficiency was 48.09%, and the minimum production cost of this system was 19.3 $/GJ. Rovira et al [21] proposed an ISCC system with the recently developed double recuperative double expansion (DRDE) cycle as the bottom cycle, and compared to the conventional ISCC system, the annual average heat consumption rate and LCOE of this novel system were lower.…”
Section: Introductionmentioning
confidence: 99%
“…The use of organic fluids in Rankine cycles leads to simple functional schemes in which, for fluids with complex molecular composition, the appearance of liquid is avoided during the expansion process in the expander. The use of high molecular weight organic fluids has the effect of reducing the enthalpy drop in the expander which leads to a decrease in its number of stages or to a decrease in the peripheral speed at the exit of the turbine [ 2 , 3 , 4 ]. The choice of organic fluids with higher critical temperatures but appropriate to those of the heat sources leads to condensation pressures higher than the ambient pressure, thus eliminating the special measures for sealing the condenser [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%